Implementasi Load Balancing Server Basis Data Pada Virtualisasi Berbasis Kontainer - Moch. Wahyu Imam Santosa; Rakhmadhany Primananda; Widhi Yahya (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Most of systems that we use nowadays still implement single database server architecture. It makes database server incapable in handling many requests. Horizontal scaling that is done with additional processing units such as nodes, instances, or even containers is a solution in increasing performance of a system in handling many requests. Load balancer is needed as a system that will be used to distribute data requests to the system of database server. In this research, the author tried to solve the problem by implementing load balancing database server in container-based virtualization. Load balancing runs using load balancer and nodeport features that provided by Kubernetes. With each of the replicas connected in a centralized storage system, it makes the data consistent. The result shows that the performance of database server is increased, with throughput that was obtained from load of 750 per second was (61,3 request per second) in 2 replicas, (61,3 request per second) in 3 replicas, (64,6 request per second) in 4 replicas, and (65.,6 request per second) in 5 replicas.